Humanitarian Intervention And The American War In Iraq Between Ideals And Practice - Hanane NOUICER (UNIVERSITÉ MOHAMED BOUDIAF - M’SILA, 2024)
This dissertation explores the relationship between the concept of humanitarian intervention and the realities of America warfare , the core tension lies in the disparity between the ideas of promoting human rights and protecting civilians ,often cited as justification for intervention and the practical consequences of war itselfs.by integrating qualitative and quantative methods this research aims to provide a comprehensive understanding of the complexities and contradiction inherent in humanitarian intervention and their implications between ideals and practice.
Keywords: Humanitarian intervention; human rights; the united state of America; invasion; Iraq; practice-ideals